(untitled) (Fiep Bulletin - online, 2014)
The current training of university teachers is beset by many challenges, due to a continuing societal claim for quality training systems that are appropriate to the changing realities and new needs. In this context, the quality of training of university teachers in physical education plays a fundamental role. This article showing results of research at Educational Research Laboratory that belongs to Universidad Nacional de La Matanza. The aim of the research is recognition quality training strategies for future PE teachers, and analysis of functions of the teaching staff in physical education from Universidad Nacional de La Matanza.